Performance of Moral Accountability and the Ethics of Satire in Stand-Up Comedy - Antti Lindfors (Museum Tusculanum Press, 2022)
This paper explores an approach to satire in stand-up comedy at the intersection of emotion and ethics. It is suggested that morally charged emotional language is particularly situated in stand-up due to the interactionally engaging features of this genre. The argument consists in framing satire as a practice and performance of moral accountability. The analysis explores how the invocation and potential dramatization of moral accountability and (intentional) agency dialectically enhance the emotional and moral efficacy of satire, and why certain habitual practices constitute fruitful targets for satire. Several cases are presented to examine how satire gives rise to dialectic of moral accountability and emotion through the use of specific stylistic and textual devices.